Impacts of Metal–Support Interaction on Hydrogen Evolution Reaction of Cobalt-Nitride-Carbide Catalyst - Zhang, Xuan; Li, Yu-An; Huang, Yaozhen; Mu, Haiqiang; Gu, Xiaofeng; Li, Feng; Wang, Zheng; Li, Jing (Frontiers in Chemistry, 2022)
Cobalt-nitride-carbide (Co-N-C) catalysts are promising cost-efficient transition metal catalysts for electrocatalytic hydrogen evolution, but few works investigate the metal–support interaction (MSI) effect on hydrogen evolution reaction (HER) performance. Herein, efficient Co-N-CX catalysts with controllable MSI between encapsulated Co nanoparticles and nitrogen-doped graphitic carbon nanosheets were synthesized via a facile organic–inorganic hybridization method. Results demonstrate that the Co-N-C0.025M catalyst with the coexistence of single-atom Co sites and Co nanoparticles prepared by 0.025 M cobalt nitrate shows excellent HER performance, achieving a low overpotential of 145 mV to reach 10 mA cm−2 in 0.5 M sulfuric acid, which is mainly because the optimal MSI, which leads to a moderate hydrogen adsorption energy and improved electroactive sites, not only facilitates the charge transfer to improve the HER kinetics, but also improves the durability of the catalyst by Co-N bond anchoring and encapsulation of active Co species. This work provides guidance to further reveal the influence of MSI on their catalytic activity.